Jewel box : stories - Yu, E. Lily (Erewhon, an imprint of Kensington Publishing Corp., 2023)
Angels, monsters, and bees. Birdwatchers, emperors, and prison wardens. These and more populate the twenty-two new and old stories from award-winning author E. Lily Yu, collected for the first time here in her debut short story collection.